(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The constant and quick changes in the healthcare industry have made performance reviews a vital tool for managers in the field. Achieving sustainable performance management entails boosting an organization’s efficacy and efficiency while taking into account all sustainability factors. This study looks at how strategic HRM enhancements, accounting information systems, and digital transformation affect the performance of organizations and sustainable development. The performance of the company is assessed in this study using the balanced scorecard (BSC). The study puts out a theoretical framework for sustainable organizational growth that combines human resources involvement with traditional and digital information technologies. In an empirical study, a questionnaire is used to poll 209 healthcare sector workers in order to evaluate the theoretical model. The research findings, which were based on structural equation modelling, demonstrated that BSC dimensions are substantially favourably impacted by the efficacy and effectiveness of the AIS and the strategic management of human resources. Furthermore, with internal process dimension having the greatest influence, using BSC to measure organizational performance has a substantial impact on sustainable growth.